Construction Contracts : Questions and Answers - Chappell, David (London; Routledgde Taylor & Francis Group., 2021)
"This fully revised and updated edition of Construction contracts : Questions and answers includes 300 questions and incorporates 42 new judicial decisions, the JCT 2016 updates and the RIBA Building Contracts and Professional Services Contracts 2018 updates"--
Keywords: Construction contracts -- Great Britain; Construction contracts -- Great Britain